Clinical value of assessment of left atrial late gadolinium enhancement in patients undergoing ablation of atrial fibrillation. (20th January 2015) - Sramko, Marek; Peichl, Petr; Wichterle, Dan; Tintera, Jaroslav; Weichet, Jiri; Maxian, Radoslav; Pasnisinova, Silvia; Kockova, Radka; Kautzner, Josef
Abstract: Background: Left atrial (LA) fibrosis begets atrial fibrillation (AF). Cardiovascular magnetic resonance (CMR) using the late gadolinium enhancement (LGE) technique might visualize the LA fibrosis and thus help to choose an appropriate strategy for treatment of AF. In this regard, we investigated whether the extent of preablation LA LGE would predict AF recurrence after ablation in a non-selected patient population. Methods: CMR was performed in 95 patients before radiofrequency ablation of AF. An interpretable scan was available in 73 patients (age, 59 ± 8 years; men, 71%; persistent/paroxysmal AF, 55/45%). The extent of LA LGE was quantified by three established thresholding techniques. In addition, CMR was used to quantify LA volume and reservoir function. The patients were followed for AF recurrence for 1.3 ± 0.8 years. Results: The arrhythmia recurred in 29 (40%) of the patients. The extent of LA LGE did not differ between paroxysmal and persistent AF and it did not predict the AF recurrence. Moreover, the extent of LA LGE did not correlate with LA volume, reservoir function and bipolar voltage. Conclusions: Our data indicate a limited value of a routine assessment of LA LGE before ablation of AF. Further experimental and clinical researches should be done before applying the method to a wide clinical practice. Highlights: This is the second largest single-center study on the predictive value of LA LGE in patients undergoing AF ablation. The extent of preablation LA LGE did not predict postablation AF recurrence, but other traditionally reported factors did. Moreover, the extent of LA LGE did not correlate with other LA characteristics that reflect the LA structural remodelling.